Recent progress in modeling ICRF-edge plasma interactions with application to ASDEX Upgrade. (1st July 2022) - Zhang, W.; Bilato, R.; Bobkov, V.; Cathey, A.; Di Siena, A.; Hoelzl, M.; Messiaen, A.; Myra, J.R.; Suárez López, G.; Tierens, W.; Usoltceva, M.; Wright, J.C.; et al.
Abstract: This paper summarizes recent progress in modeling the interaction between ion cyclotron range of frequency (ICRF) waves and edge plasma with application to ASDEX Upgrade. The basic theories, the development of ICRF and edge plasma codes, the integrated modeling methods and some key results are reviewed. In particular, the following physical aspects are discussed: (1) ICRF power coupling; (2) slow wave propagation; (3) ICRF-rectified sheath; (4) ICRF-induced convection; (5) ICRF-edge turbulence interaction. Moreover, comprehensive integrated modeling strategies by including all necessary codes in one package and solving multiple physical issues self-consistently are discussed.